硅基底上二维硒氧化铋的化学气相沉积法 合成及其光电探测应用 = Synthesis of two-dimensional Bi2O2Se on silicon substrate by chemical vapor deposition and its photoelectric detection application - Fu, Qundong (2023)
半导体加工工艺微缩过程中, 硅基材料的短沟道效应带来的低能效促使研究人员寻找新型半导体替代材料. 二维半导体因其原子级别的厚度以及范德瓦耳斯表面而倍受关注, 二维硒氧化铋就是其中迁移率、稳定性以及成本各方面较为均衡的一种. 然而, 其制备受到基底很严格的限制, 导致器件加工难度较大. 本文利用化学气相沉积法直接在硅片基底上合成出规格为25 µm×51.0 nm(厚度)的二维硒氧化铋, 并通过拉曼光谱、原子力显微镜、扫描电子显微镜、X射线能谱对其进行表征. 同时, 通过场效应晶体管输运的测试得出其迁移率为80.0 cm2/(V·s)以及光电探测得出其具有2.45×104 A/W的光响应度和6×104的光增益等比较出色的表现. 但由于厚度较大, 导致其场效应管开关比低(2500)以及不高的光电探测灵敏度(5×1010 Jones). 由此可知, 硅片基底虽然带来器件加工上的便利性, 但有待进一步优化生长, 并集成更多种材料的应用. As the scaling-down of semiconductor processing technology goes on, it is urgent to find the successor of silicon-based materials since the severe short channel effect lowers down their energy efficiency as logic devices. Owing to its atomic thickness and van der Waals surface, two-dimensional semiconductors have received huge attention in this area, among which Bi2O2Se has achieved a good trade-off among the carrier mobility, stability and costing. However, the synthesis of Bi2O2Se need some polarized substrates, which hinders its processing and application. Here, a Bi2O2Se layer with 25 µm in size and 51.0 nm in thickness is directly synthesized on a silicon substrate via chemical vapor deposition. A Field-effect transistor with a carrier mobility of 80.0 cm2/(V·s) and phototransistor with a photoresponsivity of 2.45×104 A/W and a photogain of 6×104 is also demonstrated, which hpossesses quite outstanding photodetection performance. Nevertheless, the high dark current and low on/off ratio brought by the large thickness leads to a fair detectivity (5×1010 Jones). All in all,, although silicon substrate brings convenience in device fabricating, it is still needed to further optimizing the growth and integrating more applications of various two-dimensional materials.